Added Value of Contrast‐Enhanced Spectral Mammography in Postscreening Assessment. Issue 5 (27th June 2016) - Tardivel, Anne‐Marie; Balleyguier, Corinne; Dunant, Ariane; Delaloge, Suzette; Mazouni, Chafika; Mathieu, Marie‐Christine; Dromain, Clarisse
Abstract: To assess the value on diagnostic and treatment management of contrast‐enhanced spectral mammography (CESM), as adjunct to mammography (MG) and ultrasound (US) in postscreening in a breast cancer unit for patients with newly diagnosed breast cancer or with suspicious findings on conventional imaging. Retrospective review of routine use of bilateral CESM performed between September 2012 and September 2013 in 195 women with suspicious or undetermined findings on MG and/or US. CESM images were blindly reviewed by two radiologists for BI‐RADS ® assessment and probability of malignancy. Each lesion was definitely confirmed either with histopathology or follow‐up. Two hundred and ninety‐nine lesions were detected (221 malignant). CESM sensitivity, specificity, positive‐predictive value and negative‐predictive value were 94% (CI: 89–96%), 74% (CI: 63–83%), 91% (CI: 86–94%) and 81% (CI: 70–89%), respectively, with 18 false positive and 14 false negative. CESM changed diagnostic and treatment strategy in 41 (21%) patients either after detection of additional malignant lesions in 38 patients (19%)—with a more extensive surgery ( n = 21) or neo‐adjuvant chemotherapy ( n = 1)—or avoiding further biopsy for 20 patients with negative CESM. CESM can be performed easily in a clinical assessment after positive breast cancer screening and may change significantly the diagnostic and treatment strategy through breast cancer staging.